Improved fault ride through capability in DFIG based wind turbines using dynamic voltage restorer with combined feed-forward and feed-back control - Amalorpavaraj R.A.J.; Kaliannan P.; Padmanaban S.; Subramaniam U.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fault currents; Electric machine control; Feedback; MATLAB; Reactive power; Voltage control; Voltage measurement; Voltage regulators; Wind turbines; Doubly fed induction generators; Dynamic voltage restorer (DVR); Fault ride-through (FRT); Feed forward; Low-voltage ride-through; Asynchronous generators